Postcards : the rise and fall of the world's first social network - Pyne, Lydia (2021)
Postcards are usually associated with banal holiday pleasantries, but they have been made possible by sophisticated industries and institutions, from printers to postal services. Historically, postcards' innovation and significance was their ability to send and receive messages around the world easily and inexpensively. Fundamentally, postcards are about creating personal connections: links between people, places and beliefs. 0In this book Lydia Pyne examines postcards on a global scale, to understand them as artefacts that are at the intersection of history, science, technology, art and culture. In doing so, she shows us that postcards were the first global social network, and how here, in the twenty-first century, postcards are not yet extinct